Initiation of Educators into Educational Management Secrets - Saitis, Christos (Springer International Publishing, 2018)
This book provides a comprehensive method for learning modern management processes, and applying those methods to improve leadership in educational settings. The authors include case studies and techniques to solve a variety of managerial problems so that members of the educational community may improve their abilities and skills in a range of related disciples, including: strategic planning, effective decision making, time management, management conflict strategies, oral communication, management strategies for school crises, and the development of good relations and a cooperative spirit.